Future oil spill response plans require integrated analysis of factors that influence the fate of oil in the ocean. (June 2022) - Passow, Uta; Lee, Kenneth
Abstract : Future oil spill response plans for the marine environment, with or without the application of active response measures, need to consider the complexity of interactions, which impact the fate and transport of oil. Recent studies have illustrated that oil behavior and partitioning depends on oil properties, including droplet size, and environmental conditions. In addition, we now have a better understanding of the significance of chemical oxidation and hydrodynamics on the distribution, concentration and composition of oil following accidental releases at sea. There is evidence that microbial exudates may alter oil behavior and distribution, and facilitate organism-oil interactions, and observations of oil — particle interactions suggest that sedimentation may account for the missing oil fraction in some previous post-spill calculations of mass balance.